In vitro mass propagation of Typhonium flagelliforme as affected by plant growth regulators - Galehpardsari, Motahareh Nobakht; Abdul Kadir, Mihdzar; Stanslas, Johnson (Academic Journals, 2009)
Tubers were used as explants in in vitro mass propagation of Rodent Tuber (Typhonium flagelliforme). The explants were obtained from sterile plantlets and placed in shoot induction medium containing basal salts of Murashige and Skoog (MS) and various concentrations of 6-benzylaminopurine (BAP) and α-naphthaleneacetic acid (NAA). Treatment containing 5 mg/l (w/v) of BAP with 1 mg/l (w/v) of NAA produced the highest number of shoots per explant (29.17) after 12 weeks of culture and also the highest mean fresh weight of shoots formed in treatment containing 5 mg/l (w/v) of BAP with 1 mg/l (w/v) of NAA. For ex vitroestablishment, well- rooted plantlets were transferred in potting medium containing peatmoss, perlite and vermiculite (3:1:1).